The heir dilemma - Green, Abby (Harlequin presents, 2024)
"Leaving her newborn baby with his father, Quintano Holt, broke Sadie Ryan. Except to protect them from her terrifyingly dark past, she was forced to leave. Now the danger has finally passed, she'll do anything to get her son back. Including confront the Brazilian billionaire primed to hate her ..."--Back cover.